Zn/Cu complexes constructed through selective in situ Br–Cl exchange: synthesis, structures, properties, and DFT insights into the Cu-catalyzed mechanism. Issue 16 (30th March 2022) - Si, Chang-Dai; Zhang, Jian-Bin; Pan, Feng-Feng; Wang, Peng; Liao, Tian-Lu; Zheng, Wan-He; Liu, Jia-Cheng; Yuan, Kun
Abstract : The coordination polymers of Cu(ii ) and Zn(ii ) have been synthesized. Simultaneously, the selective in situ Br–Cl exchange mechanism, structures, magnetic properties, and the fluorescence lifetimes of complexes 1 –2 are discussed in detail. Abstract : Two coordination polymers (CPs), [Cu2 (L1 )(μ3 -OH)(H2 O)] n (1 ) and [Zn4 (L)2 (4, 4′-bipy)3 ]·4H2 O n (2 ), were synthesized under solvothermal conditions. Unexpectedly, the transformation of aryl–Br to aryl–Cl (Br–Cl exchange) was observed in the formation of complex 1, which was successfully proven via energy-dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). Strikingly, Cu(ii ) ions were utilized as both coordinated atoms and as a catalyst for the in situ Br–Cl exchange in the process. In contrast, 5-(3-bromo-4-carboxyphenoxy)isophthalic acid (H3 L) did not exhibit any change in complex 2 . Moreover, the Br–Cl exchange mechanism on aromatic rings of H3 L was investigated using density functional theory (DFT) calculations. More importantly, selective in situ metal/ligand reactions are important for the discovery of new ligands and synthetic organic chemistry. In addition, complex 1 exhibits a (3, 6)-connected topological network, which shows dominant antiferromagnetic exchange in the tetranuclear Cu(ii ) unit. Complex 2 shows a (3, 4, 5)-connected topology with strong fluorescence intensity and its fluorescence lifetime (16.0 μs) was obtained using the formula [( A 1 × τ 1 2 ) + ( A 2 × τ 2 2 )]/( A 1 × τ 1 + A 2 × τ 2 ).